More mud more crocodiles : the turn in the Portrait's aestheticism" - Gjurgjan, Ljiljana Ina (Array, 2004)
The paper claims that we should look into A Portrait's aesthetics as symbolic of Stephen's artistic development. However, we must not read A Portrait only as a celebration of the artist's sacrifice for arts for arts' sake or as a statemnet about liberal traditions' separation of art from real life. Stephen's statement that he desires to create the conscience of his race or teach the Irish women to "breed race less ignoble than their own" can also be seen as an early warning about the danger of an artist getting involved in political propaganda.